PENERAPAN PENDEKATAN KONSTRUKTIVISME UNTUK MEMBANGUN PEMAHAMAN DALAM PEMBELAJARAN IPAS SISWA KELAS VI SDIT AR-RAYU - Jehan Nisak Nasution; Ryan Dwi Puspita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of the constructivist approach to build understanding among sixth-grade students at SDIT Ar-Rayu. The constructivist approach emphasizes that knowledge is not obtained passively but is actively constructed by students through direct experiences, exploration, social interaction, and reflection on the learning processes they undergo, particularly in the IPAS subject on the six continents of the world. In this learning model, the teacher acts as a facilitator who creates an open learning environment that supports students’ active engagement. This study used a descriptive method with data collection techniques including classroom observation, interviews, and documentation throughout the learning process. With a total of 23 students, the results showed that 87% of students became more active in the learning process, 82% demonstrated increased curiosity, and 78% were able to connect new knowledge with previous experiences. Learning strategies such as problem-based learning, small group discussions, experiments, and open-ended questioning encouraged students to think critically, express their opinions, and develop more meaningful understanding of the lesson content. In addition, 85% of students showed improvement in social skills such as collaboration and communication. The teacher played a key role as a facilitator in designing meaningful activities and promoting student exploration. Therefore, it can be concluded that the consistent and well-planned implementation of the constructivist approach is effective in improving the quality of students' understanding and creating a student-centered learning process.